WORK AND FAMILY LIFE BALANCE: COPING AND DISTRIBUTION STRATEGIES OF FAMILY OBLIGATIONS IN DUAL-INCOME COUPLES. - Vera-Martínez, Juan J.; Martín Chaparro, M. Pilar (Anales de Psicología / Annals of Psychology, 2009)
Within research on the attempts to conciliate/balance the la-bour/familiar role demands, it studies the differential importance and structure that have a set of coping strategies and distribution of familiar obligations for members of dual-income couples. The multidimensional scaling (SSA) allows verifying the shared and individual structure of dis-tribute-coping strategies in the couple members. Means comparison shows similarities and differences between men and women in their preferences for diverse coping responses